Strong Differences in Pedogenesis on Lava Vs. Scoria Along a Hydroclimatic Gradient on Santa Cruz Island/Galápagos Archipelago (Ecuador) – Insights From Micromorphology - Martin H. Gerzabek; Rosa M. Poch; Daniela Álvarez; Leon Ploszczanski; Franz Zehetner; Franz Zehetner (Spanish Journal of Soil Science)
Galápagos has very diverse soil resources. In a recent study, we found vastly different pedogenic development on lava vs. scoria along a hydroclimatic gradient on Santa Cruz Island (800 m elevation difference; precipitation ranging from 100 to 1,600 mm a−1). On the more porous scoria deposits, soils consistently developed towards deeper and more weathered profiles with increasing humidity, while on the lavas, soil development did not follow a consistent elevational pattern. The micromorphological investigations show an increasing degree of primary mineral weathering with increasing altitude and humidity, which was more pronounced in the profiles on scoria than on lava. The greater weathering on scoria is likely due to higher inter-particle porosity and therefore larger surface area exposed to weathering. In the arid climate zone, the soil on scoria was very shallow and the primary minerals hardly weathered, whereas the soil on lava showed a greater profile thickness and a noticeable weathering of primary minerals. Unlike the relatively homogeneous scoria deposits, the lavas show irregular flow patterns with large rock outcrop sections and small depression patches, in which soils with higher available water capacity have formed. In a previous study, we also found strongly elevated phosphorus levels in these soil patches in the arid zone. Bolstered by electron microscopy and microanalyses we show evidence that these possibly originate from tortoise nesting activities. Our results point to a complex interplay of parent material, geomorphology, climate and also the activities of the Galápagos giant tortoises in shaping the soil-scape of this unique ecosystem.